PESTEL Analysis of LAM’s Role in Strengthening Quality of Islamic Higher Education Institutions - Qomusuddin, Ivan Fanani; Fatimah, Nur; Latifah, Siti; Hidayat, Ara (Institut Darul Falah Bandung Barat, 2025)
Accreditation is a fundamental instrument in ensuring the quality of higher education, which in Indonesia is undergoing a transformation from a centralized system of the National Accreditation Board for Higher Education (BAN-PT) to a discipline-based Independent Accreditation Institution (LAM). This study aims to analyze the implementation of LAM policies using the PESTEL (Political, Economic, Social, Technological, Environmental, Legal) approach. The research method used is a qualitative method through regulatory review, official reports, and the latest scientific publications. The results of the analysis show that politically, LAM gains legitimacy through national regulations that support quality assurance autonomy; economically, there are challenges of accreditation costs that are still burdensome, especially for small universities; socially, resistance to the new system can be reduced through socialization and capacity building; technologically, the digitalization of the accreditation process still faces infrastructure gaps; environmentally, LAM has the opportunity to integrate sustainability indicators into accreditation standards; and legally, harmonization between BAN-PT and LAM needs to be continuously strengthened to avoid overlapping authorities. Thus, the implementation of LAM can be seen as a strategic step towards an accreditation system that is more relevant, efficient, and oriented towards strengthening the global competitiveness of higher education.